2016
DOI: 10.1002/2015ms000559
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the variable‐resolution CESM for modeling California's climate

Abstract: In this paper, the recently developed variable‐resolution option within the Community Earth System Model (VR‐CESM) is assessed for long‐term regional climate modeling of California at 0.25° (∼28 km) and 0.125° (∼14 km) horizontal resolutions. The mean climatology of near‐surface temperature and precipitation is analyzed and contrasted with reanalysis, gridded observational data sets, and a traditional regional climate model (RCM)—the Weather Research and Forecasting (WRF) model. Statistical metrics for model e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 75 publications
2
63
0
Order By: Relevance
“…Considering the relatively flat topography (less than 100 m) over most of CV, the $28 km grid resolution satisfies our need for modeling irrigation effects. In particular, simulations at 0.125 ($14 km) conducted in Huang et al [2016] did not show a statistically significant change in temperature statistics over California. In our study, as in Zarzycki et al [2015], general circulation patterns (e.g., wind, pressure and precipitation) do not exhibit apparent artifacts in the variable-resolution transition region.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Considering the relatively flat topography (less than 100 m) over most of CV, the $28 km grid resolution satisfies our need for modeling irrigation effects. In particular, simulations at 0.125 ($14 km) conducted in Huang et al [2016] did not show a statistically significant change in temperature statistics over California. In our study, as in Zarzycki et al [2015], general circulation patterns (e.g., wind, pressure and precipitation) do not exhibit apparent artifacts in the variable-resolution transition region.…”
Section: Introductionmentioning
confidence: 88%
“…When compared to uniformresolution global models, VRGCMs provide a cost-effective approach for reaching high resolutions over a region of interest -the regional simulations in this study at 0.25 ($28 km) resolution represent a reduction in required computation of approximately 10 times over a global uniform simulation with resolution of 0.25 . VR-CESM has been demonstrated to be effective for regional climate studies and applications at a reduced computational cost compared to uniform GCMs Rhoades et al, 2015;Huang et al, 2016]. In particular, this study is one of the first to use variable resolution for assessing the impact of a physical parameterization at high-resolution in a global Earth-system model.…”
Section: Introductionmentioning
confidence: 95%
“…Note that near-surface temperature in NARR is not assimilated and shows strong warm bias in NARR when compared to observation-based gridded dataset (Z. Yang et al 2016;Huang et al 2016;Loikith et al 2015); however, the warm bias is significantly reduced by the WRF Model as shown later. Water vapor tracers embedded into the WRF Model, version 3.4.1, allow us to trace moisture that evaporates from any predefined source (Miguez-Macho et al 2013;Dominguez et al 2016).…”
Section: A Experimental Design and Model Setupmentioning
confidence: 99%
“…They found temperature decreases to be as large as 58C in the irrigated area and an accompanying downstream cooling. Using the variableresolution Community Earth System Model (VR-CESM), Huang and Ullrich (2016) found that irrigation over the California Central Valley (CCV) cools the daily maximum near-surface temperature by 1.18C. At the global scale, Sacks et al (2008) investigated irrigation impacts using the Community Atmosphere Model (CAM) coupled with the Community Land Model.…”
mentioning
confidence: 99%
“…Application examples for static (nonmoving) mesh adaptations are provided in Zarzycki et al (2014), Rauscher and Ringler (2014), Zarzycki and Jablonowski (2015), and Huang et al (2016) (see also further references therein). Our paper focuses on dynamically adaptive grids, which track features of interest during the model simulation by locally adding or removing grid points as needed.…”
Section: Introductionmentioning
confidence: 99%